نموذج التعلم التعاوني في تنمية مهارة المحادثة لدى الدارسين المبتدئين لغير الناطقين بها - Siti Hamidah Hashim
This study aims to design cooperative learning model strategy due to the weakness in speaking skill among students thus this study proposes solution for the problem. This study follows descriptive analysis method by referring to the previous studies to meet the first objective which is to expose the weakness of students in speaking skill along with its causes. And at the same time, to meet the second objective which is to identify the suitable styles of collaborative learning under 21st (twenty-first) century learning model to implement the speaking skill. This study will also use the designation method to prepare a suitable cooperative learning model for speaking skill which is the third objective for this study. At the end of study, it reaches several results and among the most important is from the perspective of former researchers whereas the students do not speak in Arabic Language even though they are majoring in this language because of psychological factors such as shame, scare and other. The top factor comes from the absence of effective strategy for speaking skill and suitable for 21st (twenty-first) century learning. Researcher also discussed the styles of cooperative learning along with the elaboration for the process in the ten forms that included in the designated learning model.